IMPROVING MSEs PERFORMANCE THROUGH COMPETITIVE ADVANTAGE: A STUDY ON SUKABUMI CITY MSEs - Abdul Aziz, Muh (Berajah Journal, 2023)
The competitive advantage obtained by Sukabumi's typical mochi MSMEs has an impact on improving the performance of MSMEs. This research aims to analyze what factors can improve the performance of MSMEs. The research sample was 121, but the data collected was only 105 samples. So, the data was analyzed with 105 final respondents. Respondents in the research were Sukabumi typical mochi MSME entrepreneurs. The analysis tool uses AMOS assistance with the Structural Equation Modeling (SEM) method. The research results show that the 5 proposed hypotheses can be accepted as a whole. There is a significant influence of market orientation on competitive advantage with a p-value of 0.040 <0.05. There is a significant influence of innovation on competitive advantage with a p-value of 0.007 < 0.05. There is a significant influence of market orientation on the performance of MSMEs, with a p-value of 0.015 < 0.05. There is a significant influence of innovation on the performance of MSMEs with a p-value of 0.025 < 0.05. There is a significant influence of competitive advantage on the performance of MSMEs with a p-value of 0.012 < 0.05.